Feasibility Study of Catheter-directed Thrombolysis with Recombinant Staphylokinase in Deep Venous Thrombosis - Heymans, Stephane; Verhaeghe, Raymond; Stockx, Luc; Collen, Désiré (Thrombosis and Haemostasis, 1998)
The feasibility of catheter-directed thrombolysis with recombinant staphylokinase was evaluated in six selected patients with deep vein thrombosis. The patients underwent intrathrombus infusion of recombinant staphylokinase (2 mg bolus followed by a continuous infusion of 1 mg/h). Heparin was given via the catheter as a bolus (5000 U) and as a continuous infusion (1000 U/h). Complete lyis was obtained in five patients and partial lysis in one patient. Complications consisted of minor bleeding in four subjects. Symptomatic reocclusion occurred in one. Debulking of the thrombus mass by a high speed rotating impeller (n = 1) and stenting (n = 3) were used as additional interventions. An underlying anatomical abnormality was present in two patients. Long term follow up revealed normal patency in all patients and normal valve function in four patients. Symptomatic venous insufficiency with valve dysfunction was present in the two with a second thrombotic episode.Thus catheter-directed infusion of recombinant staphylokinase in patients with deep vein thrombosis appears feasible and may be associated with a high frequency of thrombolysis. Larger studies to define the clinical benefit of this treatment appear to be warranted.